Effectiveness of developmentally supportive education program on nursing knowledge of retinopathy of prematurity in neonatal intensive care unit - Bindu Kunnumpurath Sankar; Riaz Karoly Marakkar; Shalu Varghese (Wolters Kluwer Medknow Publications, 2022)
Background: Retinopathy of Prematurity (ROP) is a preventable cause of childhood blindness. India accounts for nearly 10% of the worldwide estimate of blindness and visual impairment due to ROP. Nurses are pillars of neonatal intensive care units (NICUs) and play a critical role in the prevention and management of ROP. The primary aim of this study was to evaluate the effect of developmentally supportive education program on knowledge regarding prevention and management of ROP among nurses working in NICU. Materials and Methods: A hospital based pre-experimental, one group pre-test-post-test study was carried out among 32 staff nurses working in the NICU of a tertiary care center during January to February 2019. Knowledge regarding the prevention and management of ROP was assessed before and after the implementation of developmentally supportive education program using a structured knowledge questionnaire. Results: Pre-test knowledge score was mean (Standard Deviation [SD]) 9.00 (3.68) and after the educational program post-test knowledge score was found to be mean (SD) 14.53 (2.39). Paired t-test was used to evaluate the effect of developmentally supportive education program and was found to be statistically significant (t32 = 10.09, p < 0.001). Conclusions: Developmentally supportive educational program can be used as an effective intervention for improving the knowledge regarding ROP among nurses in NICU.